A Case of Unilateral Coccidioidal Chorioretinitis in a Patient with HIV-Associated Meningoencephalitis. (7th October 2019) - Toomey, Christopher; Gross, Andrew; Lee, Jeffrey; Spencer, Doran B.
Abstract : Intraocular coccidioidomycosis is a rare condition, with the most commonly reported presentation being an idiopathic iritis in patients who live in or have traveled thorough endemic areas. A paucity of reports exists describing the chorioretinal manifestations of coccidioidomycosis. Here we report a case of unilateral coccidioidal chorioretinitis and meningoencephalitis in an AIDS patient that led to near complete unilateral loss of vision. A 48-year-old Hispanic female with poorly controlled HIV/AIDS in southern California presented with a three-week history of headache, nausea, vomiting, right eye blurry vision, and a one-day history of subjective fever. Examination of the right eye revealed vitritis and several large chorioretinal lesions scattered throughout the periphery and macula with optic disc pallor. Serum coccidioidomycoses complement fixation (CF) was positive (titers of 1 : 256). Neuroimaging revealed a new area of enhancement in the left anterior frontal lobe consistent with meningoencephalitis. The patient was treated with intravenous fluconazole and intravitreal voriconazole with resolution of systemic symptoms and vitritis but persistence of unilateral, severe chorioretinal scarring and vision loss. In conclusion, in spite of the rarity of intraocular coccidioidomycosis, one must carry a degree of suspicion for this vision- and life-threatening condition as a potential etiology of chorioretinitis in individuals with pertinent risk factors.